Suppression of the Nrf2-Dependent Antioxidant Response by Glucocorticoids and 11β-HSD1-Mediated Glucocorticoid Activation in Hepatic Cells - Kratschmar, Denise V.; Calabrese, Diego; Walsh, Jo; Lister, Adam; Birk, Julia; Appenzeller-Herzog, Christian; Moulin, Pierre; Goldring, Chris E.; Odermatt, Alex (PLOS ONE, 2012)
Background Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a key transcription factor regulating a plethora of detoxifying enzymes and antioxidant genes involved in drug metabolism and defence against oxidative stress. The glucocorticoid receptor (GR) is a ligand-induced transcription factor involved in the regulation of energy supply for metabolic needs to cope with various stressors. GR activity is controlled by glucocorticoids, which are synthesized in the adrenal glands and regenerated mainly in the liver from inactive cortisone by 11β-hydroxysteroid dehydrogenase-1 (11β-HSD1). Methods and Principal Findings Using transfected HEK-293 cells and hepatic H4IIE cells we show that glucocorticoids, activated by 11β-HSD1 and acting through GR, suppress the Nrf2-dependent antioxidant response. The expression of the marker genes NQO1, HMOX1 and GST2A was suppressed upon treatment of 11β-HSD1 expressing cells with cortisone, an effect that was reversed by 11β-HSD1 inhibitors. Furthermore, our results demonstrate that elevated glucocorticoids lowered the ability of cells to detoxify H2O2. Moreover, a comparison of gene expression in male and female rats revealed an opposite sexual dimorphism with an inverse relationship between 11β-HSD1 and Nrf2 target gene expression. Conclusions The results demonstrate a suppression of the cellular antioxidant defence capacity by glucocorticoids and suggest that elevated 11β-HSD1 activity may lead to impaired Nrf2-dependent antioxidant response. The gender-specific differences in hepatic expression levels of 11β-HSD1 and Nrf2 target genes and the impact of pharmacological inhibition of 11β-HSD1 on improving cellular capacity to cope with oxidative stress warrants further studies in vivo.